2019
DOI: 10.1088/1748-0221/14/01/p01018
|View full text |Cite
|
Sign up to set email alerts
|

Study of the depletion depth in a frontside biased CMOS pixel sensors

Abstract: Depletion of the sensitive volume for semiconductor based detectors is a key to achieve high performance. It is for instance required for charged particle detection in highly radiative environment and for X-ray spectroscopy. PIPPER-2 is a CMOS pixel sensor featuring an architecture that allows the application of the reverse bias of the pn junction from the frontside (cathode), on the electronic side, without process modification. Biasing voltages up to 45 V have been applied to sensor prototypes fabricated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…With respect to MIMOSA-34, this chip was modied by extending the radius of the diode but more importantly by choosing a substantially more sizeable opening of the p-well surrounding it. As reported in [79], the chip operated at depletion voltages of up to 40 V. Based on 55 Fe amplitude spectra and TCAD simulations, it is concluded that the chip becomes fully depleted once the depletion voltage exceeds about 15 V. The simulation depth reported is ∼ 12 µm, which corresponds to about 66% of the volume of the epitaxial layer. Based on TCAD simulations, the authors argue that a depletion layer is formed in this epitaxial layer.…”
Section: Observations Of Pipper-2mentioning
confidence: 60%
“…With respect to MIMOSA-34, this chip was modied by extending the radius of the diode but more importantly by choosing a substantially more sizeable opening of the p-well surrounding it. As reported in [79], the chip operated at depletion voltages of up to 40 V. Based on 55 Fe amplitude spectra and TCAD simulations, it is concluded that the chip becomes fully depleted once the depletion voltage exceeds about 15 V. The simulation depth reported is ∼ 12 µm, which corresponds to about 66% of the volume of the epitaxial layer. Based on TCAD simulations, the authors argue that a depletion layer is formed in this epitaxial layer.…”
Section: Observations Of Pipper-2mentioning
confidence: 60%
“…expects n = 3 for an ideal point-like diode and values as high as n ≈ 6 were reported to fit measured data [103] (details see below).…”
Section: Depleting Cps Fundamental Considerationsmentioning
confidence: 77%
“…The precise value of n > 2 is so far not established and the equation will in any case provide a rough approximation of the complex geometry only. One expects n = 3 for an ideal point-like diode and values as high as n ≈ 6 were reported to fit measured data [106] (details see below).…”
Section: Depleting Cps Fundamental Considerationsmentioning
confidence: 86%
See 1 more Smart Citation